2021
DOI: 10.3390/dj9080088
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenic Biofilms: Development, Properties, and Biomimetic Preventive Agents

Abstract: Oral biofilms will build up within minutes after cleaning of the dental hard tissues. While the application of remineralizing agents is a well-known approach to prevent dental caries, modern oral care products offer also additional active agents to maintain oral health. Human saliva contains many different organic and inorganic compounds that help to buffer organic acids produced by cariogenic microorganisms. However, most oral care products only contain remineralizing agents. To improve the benefit of those p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 111 publications
0
32
0
Order By: Relevance
“…From a chemical point of view, there is no principal difference between an attack by acids from food (erosion) and by acids produced by bacteria (caries). However, the duration of these demineralization processes is usually different (erosion: short time scale, due to the presence of acidic beverages, food, or gastric juice [ 20 ]; caries: long time scale [ 24 , 25 ], e.g., in biofilms [ 26 , 27 ]).…”
Section: Protection Of Teeth Against Caries and Erosion By Fluoride-containing Agentsmentioning
confidence: 99%
“…From a chemical point of view, there is no principal difference between an attack by acids from food (erosion) and by acids produced by bacteria (caries). However, the duration of these demineralization processes is usually different (erosion: short time scale, due to the presence of acidic beverages, food, or gastric juice [ 20 ]; caries: long time scale [ 24 , 25 ], e.g., in biofilms [ 26 , 27 ]).…”
Section: Protection Of Teeth Against Caries and Erosion By Fluoride-containing Agentsmentioning
confidence: 99%
“…Children's oral cavity occurrence is greatly affected by a frequent tooth-brushing habit and a healthy diet, which prevents the presence of caries biofilm which is the principal factor of developing caries in the presence of fermentable sugars and carbohydrates and might result in teeth demineralization. In some cases, especially in those with diabetes mellitus, the total amount of sugar is reduced but dental caries exists as a result of the presence of cariogenic biofilm [16].…”
Section: Introductionmentioning
confidence: 99%
“…ferent organomineral complexes in the prophylactic agents whose molecular composition is similar to that of the biofilm organomineral complex. From this, we can draw a preliminary conclusion that the use of prophylactics at the appropriate stage of the experiment can affect the molecular composition of biofilms [9,37], which in turn is reflected in the spectroscopic characteristics. It is clearly observed that the effect of the prophylactic agent depending on the cariogenic conditions is reflected in the position and shape of the vibrational mode of Amide I (Figure 4).…”
Section: Fingerprint Regionmentioning
confidence: 97%